2020
DOI: 10.7592/ejhr2020.8.3.dore
|View full text |Cite
|
Sign up to set email alerts
|

Intertextuality and failed taboo humour in advertising

Abstract: Humour is often exploited in advertising to enhance the positive image of a brand or corporate company, as well as to promote products or services. Advertisers seek the involvement of the audience via covert or overt references that, in their opinion, may trigger humour and, hypothetically, result in a positive customer response. However, using intertextual humour in advertising can sometimes be risky because, even though the ideal interlocutor is supposed to be familiar with the humorous reference the author … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Failed humour (boring, offensive or unrealised) has a clear negative effect (Flaherty et al 2004). The audience is often offended because of intentionally humorous advertisements; however, this has more to do with the themes involved, which are often aggressive arousal safety humour, including violation of social norms or taboos (Beard, 2008;Dore 2020). Furthermore, humour is subjective, and repeated encounters with the advertisement reduce the fun (Ackerman 2011, as cited in Djambaska et al 2016).…”
Section: Humorous Advertisingmentioning
confidence: 99%
“…Failed humour (boring, offensive or unrealised) has a clear negative effect (Flaherty et al 2004). The audience is often offended because of intentionally humorous advertisements; however, this has more to do with the themes involved, which are often aggressive arousal safety humour, including violation of social norms or taboos (Beard, 2008;Dore 2020). Furthermore, humour is subjective, and repeated encounters with the advertisement reduce the fun (Ackerman 2011, as cited in Djambaska et al 2016).…”
Section: Humorous Advertisingmentioning
confidence: 99%
“…El tabú estético se construye en la cultura, en el caso del parto, especialmente el momento de la coronación y las experiencias que citaba Clements pasa a ser tabú a través de la oclusión sistemática de estos aspectos en el arte, las representaciones populares, médicas, o el cine (Tyler En general, la gente tiende a preferir o esperar un humor alejado de temas tabú, como la edad o el género, sancionados socialmente, debido a que pueden relacionarse con la muerte o el sexo, respectivamente, y así avergonzar a la audiencia en lugar de divertirla, como demuestra Marguerita Dore analizando imágenes como la figura 2, en la que expresa el rechazo de una campaña publicitaria de Burger King por poder asemejarse a una felación (Dore, 2020).…”
Section: Tabú Estético Borradounclassified
“…Whereas, only 10 comments or 25% talked about the product she was displaying. A study by Dore (2020), concluded that using humor to advertise product and services can backfire as there is no guarantee whether it will garner the desired feedback. Even so, this case, is again an anomaly.…”
Section: Hasil Dan Pembahasanmentioning
confidence: 99%